Developing Arabic writing skills using Facebook - Wan Ahmad, Wan Rusli; Mat Daud, Nuraihan (2011)
Writing is a challenging task to many foreign language learners. This study describes an attempt to use Facebook to teach writing to Arabic learners. Facebook allows users to share messages, not only in one-to-one but also in one-to-many mode of communication. The thread of communication posted on the wall was analysed. The posts revealed that Facebook was widely used by students to communicate. A total of about 89 comments or feedback were given by peers for every writing activity, with an average of four comments made on each student’s work. Arabic was used by the students, and the feedback focussed on grammatical and spelling errors. The survey revealed that majority of the students preferred using the Facebook to develop their writing skills.